Respostas

2014-05-16T22:48:13-03:00
y = x² - 2x - 3
x² - 2x - 3 = 0
a = 1
b = -2
c = -3
        Δ = b² - 4ac
        Δ = (-2)² - 4 . 1 . (-3)
        Δ = 4 + 12
        Δ = 16
                  x =  - b ± √Δ 
                            2a
                  x =  - (-2) ± √16 
                              2 . 1
                  x' =  2 - 4  =  -2  = -1
                            2         2 
                  x" =  2 + 4  =  6  = 3        
                             2         2

RESP.: -1 e 3 (alternativa A)

Espero ter ajudado. Valeu!
1 3 1
Ajudou e muito, obrigada!!
De nada!